Effects of pictorial warning label message framing and standardized packaging on cigarette packaging appeal among young adult smokers. (September 2021) - Johnson, Andrea C.; Luta, George; Tercyak, Kenneth P.; Niaura, Raymond S.; Mays, Darren
Highlights: Gain- and loss-framed pictorial warnings reduced the appeal of cigarette packs. Plain packaging reduced appeal with and without pictorial warnings. Findings can inform decision-making about cigarette labeling and packaging. Abstract: Introduction: Pictorial warning labels and standardized "plain" packaging are policy interventions to reduce smoking, in part, by making cigarette packs and smoking less appealing. To inform potential policy decisions, this study examined the relative effects of message text framing (gain vs. loss) and cigarette packaging (standardized vs. branded) on appeal in a sample of young adult cigarette smokers. Methods: Cigarette smokers (N = 339) ages 18–30 completed two within-subjects experimental tasks. Tasks assessed the effects of message text framing (gain vs. loss) and packaging (standardized vs. branded) on cigarette packaging appeal. Task 1 was a 2 × 2 discrete choice experiment, where participants chose between each experimental pack and a standard branded cigarette pack without a pictorial warning label. Task 2 was a ranking task where participants ranked all packs on measures of appeal. Results: In Task 1, there were no significant differences in measures of appeal between packs displaying gain- vs. loss-framed message text, but all packs with pictorial warning labels significantly decreased appeal relative to standard branded packs without pictorial warning labels. Standardized packs with pictorial warning labels significantly reduced appeal relative to branded packs with pictorial warning labels and standard branded packs without pictorial warning labels. Task 2 pack rankings showed similar effects of pictorial warning labels and standardized packaging on appeal. Conclusions: Pictorial warning labels with gain- and loss-framed text were equally powerful at reducing appeal of cigarette packs in young adult smokers relative to branded packs without pictorial warning labels, especially when combined with standardized packaging.